2019
DOI: 10.1002/mrm.27821
|View full text |Cite
|
Sign up to set email alerts
|

Formalin tissue fixation biases myelin‐sensitive MRI

Abstract: Purpose Chemical fixatives such as formalin form cross‐links between proteins and affect the relaxation times and diffusion properties of tissue. These fixation‐induced changes likely also affect myelin density measurements produced by quantitative magnetization transfer and myelin water imaging. In this work, we evaluate these myelin‐sensitive MRI methods for fixation‐induced biases. Methods We perform quantitative magnetization transfer, myelin water imaging, and deuterium oxide‐exchanged zero TE imaging on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 61 publications
0
31
0
Order By: Relevance
“…Second, the variability in the type and duration of fixation can lead to variability in the MRI-based metrics. Longitudinal studies investigating tissue fixation report spatially and temporally varying effects on relaxation rates, MWF and also MP ( Dawe, Bennett, Schneider, Vasireddi, Arfanakis, 2009 , Seifert, 2019 , Shatl, Uddin, Matsuda, Figley, 2018 ). In the majority of studies we assessed, the fixation process ranged from a few days to a few weeks, which means the MR signal was likely very different between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the variability in the type and duration of fixation can lead to variability in the MRI-based metrics. Longitudinal studies investigating tissue fixation report spatially and temporally varying effects on relaxation rates, MWF and also MP ( Dawe, Bennett, Schneider, Vasireddi, Arfanakis, 2009 , Seifert, 2019 , Shatl, Uddin, Matsuda, Figley, 2018 ). In the majority of studies we assessed, the fixation process ranged from a few days to a few weeks, which means the MR signal was likely very different between studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication showed that while comparing to that with conventional method, T 1 in WM measured in the same brains was 10% underestimated with MRF in which TR was from 15 to 55 ms longer than that (from 10 to 12 ms) in our experiment . As compared to the previous in vivo studies, another possible explanation for the increased sensitivity to MT effect in WM in this ex vivo experiment would be from the potential increase of the fractional water binding with myelin and thus the MT due to the delamination and formation of vacuoles in the myelin sheath in the brain tissue fixed with formalin . Although there would be adjustable options for attenuating the MT effect, a 2P model here was used to directly address the MT effect and the proposed framework can be combined with partial or single‐shot k‐space sampling techniques for further acquisition time reduction.…”
Section: Discussionmentioning
confidence: 99%
“…The comparative atlas created in this study was based on images of perfused spinal cord specimen which may have experienced some shrinkage due to the perfusion process. Siefert et al [48] quantified the level of shrinkage in human spinal cords 1 day and 31 days post formalin fixation and found that the cross-sectional size of the spinal cords shrinks by an average of 4%, and 4.4%, respectively. Therefore, an appropriate correction factor should be taken into consideration when absolute measurement values are needed.…”
Section: Discussionmentioning
confidence: 99%